Resource Utilization in Cancer Patients with Bisphosphonate-Associated Osteonecrosis of the Jaw - Najm, Mohammed S. (2013)
BACKGROUND AND OBJECTIVE: Bisphosphonate-associated osteonecrosis of the jaw (BONJ) is an emerging oral complication that occurs most commonly in the setting of high dose bisphosphonate therapy for cancer. The purpose of this study was to estimate the health care-related costs associated with a diagnosis of BONJ in cancer patients evaluated and managed at one tertiary oral medicine practice. METHODS: This was a retrospective electronic medical record review of cancer patients with BONJ. All health care related resources were abstracted using a structured chart abstraction tool; data captured included medications, imaging studies, laboratory investigations, procedures, and visits. Standardized references were used to assign costs in 2010 US dollars. RESULTS: Ninety-two cancer patients with BONJ were identified that were followed for a median of 12 months. The median cost of a case of BONJ was $1,667 (interquartile range from $976–$3,350). Medication costs comprised the majority (42%) of the total costs, followed by procedural interventions (22%), clinic visits (19.5%), and imaging studies (13.8%). Patient factors associated with higher median costs included a greater number of involved oral quadrants and more advanced BONJ stage. CONCLUSION: There are considerable costs associated with the diagnosis and management of BONJ in cancer patients, with medications accounting for nearly half of resource expenditures.